Evaluating Role of Arthrocentesis in Management of Internal Derangement of TMJ - Hijab Farid Khan, Amna Rehman, Samreen Malik, Arifa Haque, Afshan Qamar, Navid Rashid Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Concerning the management of TMJ the complex anatomy of TMJ plays a vital role since it has its components that attached the most versatile part of human body. It has its several components performing and aiding in multitude of functions(1). Each instance of TMD is different and complex, thus diagnosis involves a thorough examination of the individual patient's history and symptoms as well as a range of methods. Objective: The objective of this study was to evaluate the role of arthrocentesis in management of internal derangement of TMJ Methodology: In order to access the relevant research articles a systemic research was conducted via three data bases including PubMed, Google Scholar and web of science.